Explaining trends in alcohol-related harms in Scotland, 1991–2011 (I): the role of incomes, effects of socio-economic and political adversity and demographic change. (March 2016) - McCartney, G.; Bouttell, J.; Craig, N.; Craig, P.; Graham, L.; Lakha, F.; Lewsey, J.; McAdams, R.; MacPherson, M.; Minton, J.; Parkinson, J.; Robinson, M.; et al.
Abstract: Objective: This paper tests the extent to which differing trends in income, demographic change and the consequences of an earlier period of social, economic and political change might explain differences in the magnitude and trends in alcohol-related mortality between 1991 and 2011 in Scotland compared to England & Wales (E&W). Study design: Comparative time trend analyses and arithmetic modelling. Methods: Three approaches were utilised to compare Scotland with E&W: 1. We modelled the impact of changes in income on alcohol-related deaths between 1991–2001 and 2001–2011 by applying plausible assumptions of the effect size through an arithmetic model. 2. We used contour plots, graphical exploration of age-period-cohort interactions and calculation of Intrinsic Estimator coefficients to investigate the effect of earlier exposure to social, economic and political adversity on alcohol-related mortality. 3. We recalculated the trends in alcohol-related deaths using the white population only to make a crude approximation of the maximal impact of changes in ethnic diversity. Results: Real incomes increased during the 1990s but declined from around 2004 in the poorest 30% of the population of Great Britain. The decline in incomes for the poorest decile, the proportion of the population in the most deprived decile, and the inequality in alcohol-related deaths, were all greater in Scotland than in E&W. The model predicted less of the observed rise in Scotland (18% of the rise in men and 29% of the rise in women) than that in E&W (where 60% and 68% of the rise in men and women respectively was explained). One-third of the decline observed in alcohol-related mortality in Scottish men between 2001 and 2011 was predicted by the model, and the model was broadly consistent with the observed trends in E&W and amongst women in Scotland. An age-period interaction in alcohol-related mortality was evident for men and women during the 1990s and 2000s who were aged 40–70 years and who experienced rapidly increasing alcohol-related mortality rates. Ethnicity is unlikely to be important in explaining the trends or differences between Scotland and E&W. Conclusions: The decline in alcohol-related mortality in Scotland since the early 2000s and the differing trend to E&W were partly described by a model predicting the impact of declining incomes. Lagged effects from historical social, economic and political change remain plausible from the available data. Highlights: Alcohol-related mortality in Scotland has increased then decreased since the 1980s. To evaluate the impact of alcohol policy we need to understand the causes of these trends. Income trends and alcohol affordability explain part of the rise and fall. Adults aged 40–70 years during the 1990s and 2000s experienced the greatest change. Lagged effects from historical change remain plausible from the available data.